Vygotsky's sociocultural theory in the context of globalization. Issue 1 (2nd January 2017) - Marginson, Simon; Dang, Thi Kim Anh
Abstract: The article reviews the social-educational theorization of the early Soviet psychologist L. S. Vygotsky (1896–1934) in the light of the impact of communicative globalization in educational practice. Vygotsky proposed four "genetic domains" for investigating higher cognitive processes: the phylogenetic (humans undergoing natural evolution), the cultural-historical (social activity of humans), the ontogenetic (individual lifespan), and the microgenetic (immediate events). Vygotskian sociocultural theory is widely used in educational research, especially Vygotsky's notion of mediated development via tools and signs. Since Vygotsky, communicative globalization has transformed educational potentials. Nevertheless, provided adjustments are made to Vygotsky's genetic method to incorporate time-space compression, the mutual presence of the genetic domains, and the glonacal heuristic, Vygotskian theory continues to be useful in socially-situated investigations of educational development and transformation, and opens another way into the global, for example investigation of the role of global mediation in learning.